Pengaruh Profitabilitas, Solvabilitas, Likuiditas, dan Ukuran Perusahaan terhadap Audit Delay - Amir Mahmud; Muslimin Muslimin (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to examine the effect of profitability, solvency, liquidity, and firm size on audit delay in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Audit delay refers to the period between the company’s fiscal year-end and the issuance date of the independent auditor’s report. This research employed a quantitative approach using panel data regression analysis. The sample was selected using purposive sampling, resulting in 75 companies with a total of 225 observations. Profitability was measured using Return on Assets (ROA), solvency using Debt to Equity Ratio (DER), liquidity using Current Ratio (CR), and firm size using the natural logarithm of total assets. Based on the model selection tests, the Fixed Effect Model (FEM) was determined as the most appropriate model. The results indicate that profitability has no significant effect on audit delay. Solvency and liquidity have a positive and significant effect on audit delay, while firm size has a negative and significant effect on audit delay. These findings suggest that higher debt levels and greater complexity of current assets may extend the audit process, whereas larger companies tend to have better internal control systems that enable faster audit completion. This study is expected to contribute to the development of audit delay literature and provide consideration for companies and auditors in improving the timeliness of financial reporting